USING CASES IN MATHEMATICAL ANALYSIS - Akhmedova Gavhar Akhadovna; Karimova Azizabonu Nozimjon kizi (Bright Mind Publishing, 2025)
This article discusses the effectiveness of using the case method in teaching mathematical analysis in the higher education system. Compared to traditional teaching methods, teaching based on cases allows students to develop independent thinking skills, form the ability to apply theoretical knowledge in practice, and strengthen critical thinking competencies in analyzing and solving problem situations. The article analyzes in detail the stages of selecting, compiling cases, and integrating them into the teaching process. Also, based on the results of research conducted in the experimental group, the positive results of the case method in the educational process are substantiated. In the conclusion, practical recommendations are given for expanding the use of case technologies in mathematical analysis.
Keywords: Mathematical analysis, case method, case technology, interactive learning, practical problem, student activity, critical thinking, independent learning, innovative approach, lesson effectiveness.